Individual differences in the reminiscence bump of very long-term memory for popular songs in old age: A non-linear mixed model approach. (July 2020) - Zimprich, Daniel
Recognition of popular songs from one's past shows a phenomenon that is known as a "reminiscence bump" from autobiographical memory research, namely, the increased recognition performance of songs from one's youth and early adulthood. As a first goal of the present study, a non-linear functional relation between popular song recognition performance and song-specific age of an individual was examined. As a second goal, individual differences in recognition performance curves were taken into account by including random effects. The third goal was to explain individual differences by including predictor variables. The sample comprised 90 participants aged 70 to 75 years. Participants listened to excerpts of 51 songs of the German charts from the years 1945 to 1995. Results show that the average bump performance was 75%, that the bump was located at about 17 years of age, and that the inflection point was located at 31 years. Individual differences could be explained by the number of correctly recognized songs, musical taste during one's youth, and the frequency and preference of listing to bump songs. To conclude, an individual differences approach based on a non-linear function relation has been found to be a promising way to understand why popular songs from one's youth are remembered better.